Determining Bank performance using CAMEL rating: A comparative study on selected Islamic and Conventional Banks in Bangladesh - Rafiq, Md. Rafiqul Islam (Asian Business Review, 2016)
The present article seeks to examine the determinants of the bank profitability in a developing country like Bangladesh and to compare the performance of Islamic and conventional banks during the period 2008 - 2014. Specifically working within the Bangladeshi financial sector, the analysis is confined to the domestic commercial banks operating in the Bangladeshi financial sector during the period 2008-2014. In order to achieve the study objectives and to answer some questions, the ratio analysis and CAMEL has been used. The study found that the higher capital ratio, Tier-1, and growth in total deposits for Islamic banks than conventional banks. On the other hand, Islamic banks are not able to good perform with ROA, ROE and cost-to-income ratio while conventional banks showed satisfactory performance in utilizing funds which was proved in this analysis as high ROA, ROE and cost-to-income ratio. This study shows that management efficiency regarding operating expenses positively and significantly affects the banks’ profitability. JEL Classifications: G2, G22, H12, G14The present article seeks to examine the determinants of the bank profitability in a developing country like Bangladesh and to compare the performance of Islamic and conventional banks during the period 2008 - 2014. Specifically working within the Bangladeshi financial sector, the analysis is confined to the domestic commercial banks operating in the Bangladeshi financial sector during the period 2008-2014. In order to achieve the study objectives and to answer some questions, the ratio analysis and CAMEL has been used. The study found that the higher capital ratio, Tier-1, and growth in total deposits for Islamic banks than conventional banks. On the other hand, Islamic banks are not able to good perform with ROA, ROE and cost-to-income ratio while conventional banks showed satisfactory performance in utilizing funds which was proved in this analysis as high ROA, ROE and cost-to-income ratio. This study shows that management efficiency regarding operating expenses positively and significantly affects the banks’ profitability. JEL Classifications: G2, G22, H12, G14